2012
DOI: 10.5047/eps.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind electron interaction with the dayside lunar surface and crustal magnetic fields: Evidence for precursor effects

Abstract: Electron distributions measured by Lunar Prospector above the dayside lunar surface in the solar wind often have an energy dependent loss cone, inconsistent with adiabatic magnetic reflection. Energy dependent reflection suggests the presence of downward parallel electric fields below the spacecraft, possibly indicating the presence of a standing electrostatic structure. Many electron distributions contain apparent low energy (<100 eV) upwardgoing conics (58% of the time) and beams (12% of the time), primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…At locations relatively far from the presence of the crater, we found photoelectron sheath potentials and electric fields typical of that from previous estimations, simulations, and observations (Freeman and Ibrahim, 1975;Halekas et al, 2008;Poppe and Horányi, 2010). Interestingly, these simulations do not show the presence of a non-monotonic potential layer above the surface of the Moon while in the solar wind, as previous simulations and observations have indicated (Poppe and Horányi, 2010;Poppe et al, 2011Poppe et al, , 2012Halekas et al, 2012). We attribute this to the simulation volume to which our computational constraints limit us.…”
Section: Discussionsupporting
confidence: 80%
“…At locations relatively far from the presence of the crater, we found photoelectron sheath potentials and electric fields typical of that from previous estimations, simulations, and observations (Freeman and Ibrahim, 1975;Halekas et al, 2008;Poppe and Horányi, 2010). Interestingly, these simulations do not show the presence of a non-monotonic potential layer above the surface of the Moon while in the solar wind, as previous simulations and observations have indicated (Poppe and Horányi, 2010;Poppe et al, 2011Poppe et al, , 2012Halekas et al, 2012). We attribute this to the simulation volume to which our computational constraints limit us.…”
Section: Discussionsupporting
confidence: 80%
“…These works also suggested, somewhat un-intuitively, that the non-monotonic potential may in fact be energetically preferred over the monotonic solution. In-situ measurements by the Lunar Prospector (LP) Electron Reflectometer (ER), which orbited the Moon and could sense the lunar surface potential via electron reflectometry, suggested that non-monotonic potentials were indeed present [Halekas et al, 2008b[Halekas et al, , 2012. By comparing with a one-dimensional particle-in-cell simulation, these measurements were confirmed as resulting from nonmonotonic potentials [Poppe and Horányi, 2010;Poppe et al, 2011].…”
Section: Introductionmentioning
confidence: 95%
“…Preliminary comparisons of PIC model results with plasma sheet data from LP show very encouraging consistency, lending credence to the existence of nonmonotonic potentials above the dayside surface in at least one plasma regime [ Poppe et al , 2011]. Solar wind data also provide hints of such structures, though LP did not have energy resolution and coverage sufficient to make definitive conclusions [ Halekas et al , 2011]. The terrestrial magnetotail lobes, meanwhile, which have plasma densities so low (<∼0.1 cm −3 ) that spacecraft charge to rather large positive potentials and spacecraft photoelectrons dominate measurements, present a very difficult environment in which to remotely measure surface charging.…”
Section: Introductionmentioning
confidence: 99%